Legal Dynamics in the Era of Digitalization and Globalization: Challenges for Legal Professional Institutions in the Future (Open Society Conference, 2025)
The digitalization of legal institutions, along with technological developments, requires legal institutions to keep pace with current digital developments and to have the necessary technological or digital infrastructure to develop within their institutions. Legal development in Indonesia is crucial in the digital era, as technology continues to advance. Increasing the legal profession's knowledge of technology will only make their work easier. In legal institutions, a significant amount of data must be kept confidential. Issues arise regarding the security of legal data, such as important files and legal documents, which must be properly stored and safeguarded. In today's digital age, new crimes, such as hackers, are becoming increasingly widespread and rampant, as they easily breach computer security systems. This article is a normative legal research. Normative legal research is a research method used to conduct research on secondary sources. The results of this research suggest that legal institutions must be more vigilant in securing important documents within legal institutions to ensure the smooth running of law in Indonesia.